Language in culture : lectures on the social semiotics of language - Silverstein, Michael (Cambridge University Press, 2023)
Language enables us to represent our world, rendering salient the identities, groups, and categories that constitute social life. Michael Silverstein (1945–2020) was at the forefront of the study of language in culture, and this book unifies a lifetime of his conceptual innovations in a set of seminal lectures. Focusing not just on what people say but how we say it, Silverstein shows how discourse unfolds in interaction. At the same time, he reveals that discourse far exceeds discrete events, stabilizing and transforming societies, politics, and markets through chains of activity. Presenting his magisterial theoretical vision in engaging prose, Silverstein unpacks technical terms through myriad examples – from brilliant readings of Marcel Marceau's pantomime, the class-laced banter of graduate students, and the poetics/politics of wine-tasting, to Fijian gossip and US courtroom talk. He draws on forebears in linguistics and anthropology while offering his distinctive semiotic approach, redefining how we think about language and culture. -- Présentation de l'éditeur.